2021
DOI: 10.3390/cancers13020189
|View full text |Cite
|
Sign up to set email alerts
|

The Caspase-1/IL-18 Axis of the Inflammasome in Tumor Cells: A Modulator of the Th1/Tc1 Response of Tumor-Infiltrating T Lymphocytes in Colorectal Cancer

Abstract: In colorectal cancer (CRC), a high density of T lymphocytes represents a strong prognostic marker in subtypes of CRC. Optimized immunotherapy strategies to boost this T-cell response are still needed. A good candidate is the inflammasome pathway, an emerging player in cancer immunology that bridges innate and adaptive immunity. Its effector protein caspase-1 matures IL-18 that can promote a T-helper/cytotoxic (Th1/Tc1) response. It is still unknown whether tumor cells from CRC possess a functional caspase-1/IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Due to its immune-stimulating and anti-cancer actions, IL-18 has been proposed as a viable adjuvant therapy for cancer [15][16][17] . However, IL-18 has been linked to the advancement of the disease and in some malignancies, with the likelihood of recurrence and is raised in the blood of the majority of cancer patients [17][18][19] . It is also addressed how Rhodomyrtone, a bioactive substance found in Rhodomyrtus tomentosa leaves, prevents A431 epidermoid carcinoma cells from spreading malignancy 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its immune-stimulating and anti-cancer actions, IL-18 has been proposed as a viable adjuvant therapy for cancer [15][16][17] . However, IL-18 has been linked to the advancement of the disease and in some malignancies, with the likelihood of recurrence and is raised in the blood of the majority of cancer patients [17][18][19] . It is also addressed how Rhodomyrtone, a bioactive substance found in Rhodomyrtus tomentosa leaves, prevents A431 epidermoid carcinoma cells from spreading malignancy 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Casp1 enzymatically processes the inactive precursor (pro-IL-18) into the mature form of IL-18 17 . Through the stimulation of NK and/or T cell responses, IL-18 has been studied in clinical trials on cancer patients and has demonstrated anti-tumour effectiveness in numerous preclinical models of cancer immunotherapy 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The pro-tumorigenic role of IL-18 has been well-studied [ 34 , 35 , 36 ], and its high availability in the serum makes it a prime candidate as an indicator for epithelial reaction and metastasis formation [ 37 , 38 , 39 ]. Previous research has already established the role of IL-18 in mediating the Th1/tumor-infiltrating lymphocyte response [ 13 ]. Similarly, high levels of IL-6 in hepatocellular carcinoma correlate with poor survival prognosis and recurrence [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The caspase-1/IL-18 (IL-1ß) axis has additionally been evaluated in tumor-related disease. A recent study has shown that IL-18 correlates with the local Th1/tumor-infiltrating lymphocyte response in colorectal [ 13 ] as well as in breast cancer [ 14 ]. Moreover, it could be shown that the neutrophil-to-lymphocyte ratio and C-reactive protein [ 15 , 16 ], as well as other inflammatory cytokines, are regulated in the environment of neuroendocrine tumors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study by Mutala et al (2021) reported that tumor cells of most CRCs display a functional and activated caspase-1/IL-18 axis that can modulate the IFN-γ response elicited by the Th1/Tc1 response. Moreover, the authors strongly suggested that targeting the inflammasome pathway could improve the antitumor immune response in subgroups of CRC [ 143 ]. Another study reported that the inhibition of NLRP3 inflammasome assembly in macrophages was responsible for the preventive effect of arctigenin against CAC in patients with colitis [ 144 ].…”
Section: Inflammasome and Intestinal Tumorigenesismentioning
confidence: 99%